-7x - 2y = -13
-7x + 7x - 2y = 7x - 13
-2y = 7x - 13
-2 -2
y = -3.5x + 6.5
x - 2y = 11
x - 2(-3.5x + 6.5) = 11
x - 2(-3.5x) - 2(6.5) = 11
x + 7x - 13 = 11
8x - 13 = 11
+ 13 + 13
8x = 24
8 8
x = 3
y = -3.5x + 6.5
y = -3.5(3) + 6.5
y = -10.5 + 6.5
y = -4
(x, y) = (3, -4)
A><span><span>−b</span>−<span>4
Hope this helps. c:</span></span>
_Brainliest if helped!
1 over 64
8^2 = 64 , 8^-2 = 1/(8^2) = 1/64
Answer:
55.64
Step-by-step explanation:
The range finder is 92 feet from the building and 106 feet from the top of the building i.e. hypotheses
We will use the Pythagorean theorem:
x^2 = 106^2 - 92^2
= 11,236 - 8,464
= 2,772
= √2,772
x =
52.64978632
The height of the building:
h = x + 3
= 52.64978632
+ 3
= 55.64978632
or
≈ 55.64 feet
Answer:
60cm³
Step-by-step explanation: